Evolutionary Maintenance of the PTS2 Protein Import Pathway in the Stramenopile Alga Nannochloropsis - Kechasov, Dmitry; de Grahl, Imke; Endries, Pierre; Reumann, Sigrun (Frontiers in Cell and Developmental Biology, 2020)
The stramenopile alga Nannochloropsis evolved by secondary endosymbiosis of a red alga by a heterotrophic host cell and emerged as a promising organism for biotechnological applications, such as the production of polyunsaturated fatty acids and biodiesel. Peroxisomes play major roles in fatty acid metabolism but experimental analyses of peroxisome biogenesis and metabolism in Nannochloropsis are not reported yet. In fungi, animals and land plants, soluble proteins of peroxisomes are targeted to the matrix by one of two peroxisome targeting signals (type 1, PTS1, or type 2, PTS2), which are generally conserved across kingdoms and allow the prediction of peroxisomal matrix proteins from nuclear genome sequences. Because diatoms lost the PTS2 pathway secondarily, we investigated its presence in the stramenopile sister group of diatoms, the Eustigmatophyceae, represented by Nannochloropsis. We detec-ted a full-length gene of a putative PEX7 ortholog coding for the cytosolic receptor of PTS2 proteins and demonstrated its expression in N. gaditana. The search for predicted PTS2 cargo proteins in N. gaditana yielded several candidates. In vivo subcellular targeting analyses of representative fusion proteins in different plant expression systems demonstrated that two predicted PTS2 domains were indeed functional and sufficient to direct a reporter protein to peroxisomes. Peroxisome targeting of the predicted PTS2 cargo proteins was further confirmed in N. oceanica by confocal and transmission electron microscopy. Taken together, the results demonstrate for the first time that one group of stramenopile algae maintained the import pathway for PTS2 cargo proteins. To comprehensively map and model the metabolic capabilities of Nannochloropsis peroxisomes, in silico predictions needs to encompass both the PTS1 and the PTS2 matrix proteome.